Celebrating the Art of Theatre in Heidelberg. Festival review: International Hot Shorts – Short Play Festival, organized by the Schauspielgruppe des Anglistischen Seminars, e.V. in partnership with the UNESCO City of Literature Heidelberg, 2-9 July 2016 - WOHL, Eugen (Studia Universitatis Babeș-Bolyai Dramatica, 2017)
I may be accused of being highly subjective when saying that one immediately falls in love with the splendid city of Heidelberg, but it is a risk I am willing to take. The city’s famous landmark – the romantic ruined castle that safeguards it from the hilltop –, its impressive architecture, the Bohemian streets, squares, cafés and restaurants, the abundance of cultural events, its prestigious university and the effervescent student life are all more than sufficient reasons for travelers to, at least once in their lifetime, visit the German town on the banks of the river Neckar.